2000
DOI: 10.1007/s11881-000-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Is dyslexia a form of specific language impairment? a comparison of dyslexic and language impaired children as adolescents

Abstract: Two groups of adolescents with a childhood history of language impairment were compared with a group of developmentally dyslexic young people of the same age and nonverbal ability. The study also included two comparison groups of typically developing children, one of the same age as those in the clinical groups, and a younger comparison group of similar reading level to the dyslexic students. Tests of spoken and written language skills revealed that the adolescents with dyslexia were indistinguishable from tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 30 publications
5
56
0
5
Order By: Relevance
“…Weaknesses compared to control levels in literacy and phonological measures were as large, if not larger, amongst the other SEN groups, particularly the SLD and MLD groups (see Figure 1). These data were consistent with findings for deficits in literacy (reading and spelling) and phonological processing (awareness, memory and rapid access) amongst children with generally low scores on IQ-based tests (Ellis et al, 1996;Share, 1996;Siegel, 1988;Stanovich & Siegel, 1994;Stanovich & Stanovich, 1997) and amongst children with a history of language impairments (Bishop et al, 1999;Briscoe, Bishop, & Norbury, 2001;Catts et al, 2002;Goulandris, Snowling, & Walker, 2000;Van Alphen et al, 2004;Wiig, Zureich, & Chan, 2000). The findings of such studies, and the data reported in the present paper, suggest that either the majority of children with dyslexia, MLD and SLD should be treated identically in educational programmes designed to remediate literacy-related weaknesses or that further measures need to be considered to specifically differentiate each of these SEN groups from normal development.…”
Section: Discussionsupporting
confidence: 85%
“…Weaknesses compared to control levels in literacy and phonological measures were as large, if not larger, amongst the other SEN groups, particularly the SLD and MLD groups (see Figure 1). These data were consistent with findings for deficits in literacy (reading and spelling) and phonological processing (awareness, memory and rapid access) amongst children with generally low scores on IQ-based tests (Ellis et al, 1996;Share, 1996;Siegel, 1988;Stanovich & Siegel, 1994;Stanovich & Stanovich, 1997) and amongst children with a history of language impairments (Bishop et al, 1999;Briscoe, Bishop, & Norbury, 2001;Catts et al, 2002;Goulandris, Snowling, & Walker, 2000;Van Alphen et al, 2004;Wiig, Zureich, & Chan, 2000). The findings of such studies, and the data reported in the present paper, suggest that either the majority of children with dyslexia, MLD and SLD should be treated identically in educational programmes designed to remediate literacy-related weaknesses or that further measures need to be considered to specifically differentiate each of these SEN groups from normal development.…”
Section: Discussionsupporting
confidence: 85%
“…Poor readers with the latter profile (i.e., children with LLD) have only recently received attention in research and practice. This work has shown that children with LLD may differ from other poor readers (primarily children with dyslexia) in terms of neurological structure/function and, perhaps, speech perceptual abilities (Goulandris et al, 2000;Heath et al, 1999;Joanisse et al, 2000;Leonard, 2001). However, this work is far from conclusive, and more effort is needed to understand the nature of the reading and language problems these children experience.…”
Section: Subgroup Prevalencementioning
confidence: 91%
“…Some, on the other hand, have referred to these children as having language-learning disabilities (LLD) in order to highlight their language deficits (Catts & Kamhi, 1999;Lombardino, Leonard, & Eckert, 2001). It is only recently, however, that these children have been the focus of research investigations (Goulandris, Snowling, & Walker, 2000;Heath, Hogben, & Clark, 1999;Joanisse, Mannis, Keating, & Seidenberg, 2000;Leonard, 2001). Therefore, little is known about the prevalence or nature of this subgroup of poor readers.…”
mentioning
confidence: 99%
“…The phonological system is part of the language processing system. Dyslexia is an anomaly of development because phonological processing is selectively impaired in dyslexic people while other aspects of their language, for instance their vocabulary and grammatical skills, are normal (Goulandris, Snowling and Walker, 2000). To the extent that learning to read depends upon phonological skills, dyslexic individuals are impaired.…”
mentioning
confidence: 99%